Canonical Concept of Folksong from the 18th Century until Nowadays - Sadauskienė, Jurga (Tautosakos darbai, 2021)
The article presents an overview of the traditional Lithuanian folksong concept that has prevailed since the birth of the Lithuanian folkloristics until nowadays. Having surveyed statements of the Lithuanian folksong researchers regarding the value of songs, the author compares different historical periods to elucidate the changing attitude towards this kind of folklore. Throughout the 19th century and at the beginning of the 20th century, the emphasis in the song evaluations rested on the ethical and esthetical criteria as well as on the linguistic purity, folksongs being appreciated as expressions of the national spirit. Such view resulted in numerous popular folksongs being excluded from the published folklore collections, since they did not correspond to the values of the publisher. However, as early as in the 19th century, two rival notions of the folksong tradition started forming – the conservative and the fluid one. The first one idealized the old folksong layer, while the second one regarded the folksong tradition as multisided, changing, and affected by external influences. In the middle of the 20th century, the folksong canon experienced yet another major shift. The Soviet regime neglected the major part of the later folksongs based on the individual authorship, while the ethnographic movement of the 1960s – 1980s strengthened the new tendency in the folklore canon, enhancing the value of authenticity related to the rustic roots and the old traditional heritage. Meanwhile, quite different tendencies prevailed in the exile – authenticity there was restricted to those forms of the folklore repertoire and stylistic expression that had existed in the interwar period. Having surveyed the research works and publications, manuals for folklore collectors and various statements by cultural leaders, the author concludes that complicated historical and political situation of the last two centuries has lead traditional Lithuanian folksong to play the role of the representative of the national spirit; therefore, songs were exhibited for quite a long period as phenomena of particular artistic and ethical value. Historical circumstances cause even nowadays various social groups to identify themselves not only with different content planes of the folksong repertoire, but also with different styles of performance. Only the recent decades saw folklorists gradually abandoning the exaltations and idealizations of the traditional folksongs and replacing them with discussion that is more balanced: regarding folksong tradition as ambivalent, heterogeneous and therefore meriting controversial evaluations. However, the folklorism movement still exhibits the tendency of romanticizing the old folklore and making it grounds for constructing personal identity. On the other hand, there is another clear tendency: the old folksongs – both performed in traditional manner and in modern arrangements – exist as a certain part of subculture, while another popular repertoire flourishes in the contemporary society, however, essentially escaping attention of folklorists and so far underresearched as expression of national and social identity,
Keywords: folksong; canon; folklore; ethnographic movement; arranged song